The effects of ankle dorsiflexor fatigue on lower limb biomechanics during badminton forward forehand and backhand lunge - Tong, Jianhua; Lu, Zhenghui; Cen, Xuanzhen; Chen, Chaoyi; Ugbolue, Ukadike Chris; Gu, Yaodong (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Local muscle exhaustion may have an adverse effect on the biomechanics of the lunge movement and athletic performance. This study compares the biomechanical indicators of the forward lunge in badminton players before and after exhaustion of the ankle dorsiflexors. Methods: Using the isometric muscular strength testing system, 15 badminton players underwent an ankle dorsiflexor fatigue test (CON-TREX-MJ, GER). Before and after the exhaustion experiment, five lunges were done in both the forehand forward (FH) and backhand forward (BH) directions. During the landing time, a Vicon (Oxford Metrics Ltd., Oxford, UK) motion capture system and an AMTI force measuring station (model OR6; AMTI, Watertown, Massachusetts, USA) were used to record lower limb kinematic and ground reaction force (GRF). Pre-fatigue and post-fatigue variability were determined using paired-samples t-tests, Wilcoxon signed anecdotal tests, and nonparametric mapping (SNPM). Result: The results showed that the peak ankle plantarflexion-dorsiflexion angle was significantly decreased and the range of motion (ROM) was significantly increased during the FH. Significantly increased ankle inversion ROM during FH and BH. Peak knee flexion angle and ROM were significantly greater during the FH and BH. The FH had a significantly decreased knee inversion ROM. Peak hip flexion angle and ROM were significantly reduced in the FH. During the BH, both the mean loading rate and the maximum loading rate increased significantly. The frontal offset of the center of pressure (COP) was significantly greater in the FH and BH. Conclusion: These results demonstrate impaired biomechanics of the FH and BH when the ankle dorsiflexors are fatigued, which may affect the performance of the lunge.